Global Energy-saving Map of Strong Ocean Currents. (22nd June 2015) - Chang, Yu-Chia; Tseng, Ruo-Shan; Chu, Peter C; Shao, Huan-Jie
Abstract : This study provides a global, detailed, and complete energy-saving map of strong ocean currents from the absolute geostrophic velocities calculated from satellite altimetry data, with the focus on the strong Western Boundary Currents (WBCs) in the global ocean. Theoretically, the WBCs with speeds of 2–3 knots can reduce fuel consumption by 25–50% for vessels at a sailing speed of 6 knots. The fuel savings are greater for a lower sailing speed than for a higher sailing speed. For about 1·8 million motorised fishing vessels with a lower ship speed, strong currents can evidently save fuel, time and money. Since global fishing vessels generate roughly 130 million tonnes of CO2 per annum (FAO, 2012), effective utilisation of the energy-saving map could significantly reduce CO2 emissions from ship operations.